The vascular and morphological characteristics of tumors under narrow-band imaging as predictors for the grade and stage of bladder cancer: a prospective and multi-center study - Hao Liang; Qingya Yang; Hui Sun; Yang Xu; Jin Wang; Wei Huang; Nan Ge; Qiang Fu; Tongxiang Diao; Xuewen Jiang; Shouzhen Chen; Yan Li; et al. (Annals of Medicine, 2023)
AbstractThe vascular and morphological features of tumors are important predictors of the nature, grade, and stage of various cancers. However, this association has not been tested in bladder cancer. The aim of our study was to investigate the correlation between the morphological characteristics of tumor vessels and the nature, stage and grade of bladder cancer. Between November 2021 and March 2023, we prospectively collated clinical information and cystoscopy information from a series of patients with bladder cancer. Univariate and multivariate logistic regression analysis were used to identify independent risk factors for the nature, grade and stage of bladder cancer. Our analysis showed that cauliflower-like tumors, dotted vessels, and circumferential vessels were independent risk factors for bladder cancer. Reticular vessels were an independent risk factor for high-grade bladder cancer. Thick branching vessels in bladder tumors, along with a wide base, were independent risk factors for the invasion of bladder cancer into the lamina propria. Primary diagnosis, lesion location (beside the left ureteral orifice) and obscure lesion boundaries were all identified as independent risk factors for muscle invasive bladder cancer.